Brave Batgirl! - Webster, Christy; Doescher, Erik; DC Super; Penguin Random House; Random House Children's Books; WB Television Network (New York Random House, 2017)
Introduces Batgirl, who works to keep the streets of Gotham City safe
English Stories
2
Keywords: Batgirl -- (Fictitious character); Batgirl -- (Fictitious character) -- Juvenile fiction; Batgirl -- (Fictitious character) -- Fiction; JUVENILE FICTION / Comics & Graphic Novels / Superheroes; JUVENILE FICTION / Girls & Women; JUVENILE FICTION / Media Tie-In; Superheroes -- Juvenile fiction; Superheroes; Superheroes -- Fiction; Batgirl (Fictitious character) -- Fiction; Superheroes -- Fiction; Fiction; JUVENILE FICTION / Media Tie-In; Juvenile works